The origins of Balto-Slavic accentual mobility - Kortlandt, Frederik (Baltistica, 2013)
Vedic had a restricted tone system which can also be assumed for Proto-Indo-European. Various proposed rules generating the characteristic lateral mobility of Balto-Slavic accentuation are superfluous if one starts from a strict comparative analysis of the Indo-European nominal flexion. There is an essential difference between Baltic and Slavic accentual mobility: Baltic mobility is between the root and the ending of a word form whereas Slavic mobility is between the initial and the final syllables of a phrase, including clitics. The rise of distinctive tone in Slavic was more recent than the generalization of accentual mobility in the masculine o‑stems without an acute root vowel. Linguistic contact with speakers of a language with fixed initial accent gave rise to an initial High tone which either replaced the original High tone under certain conditions or yielded doubly accented word forms with two High tones. It never yielded “unaccented” word forms with Low tones only, which originated in Vedic under certain syntactic conditions and arose in Kyōto Japanese as a result of an accent retraction. The latter development may be compared with the rise of “unaccented” word forms in Slavic.
Keywords: Balto-Slavic; historical accentology; accentuation; acentual mobility